(untitled) (Książnica Śląska, 2025)
The author presents publications related to the Siedlce region in a broad historical context. After reflections on the region and regionalism, he describes the territorial and administrative changes in southern Podlasie. First of all are presented bibliographic publications and regional scientific journals. Then he brings up works about religion, art and the most valuable monuments. The writer focuses above all on the presentation of publications on the history of Siedlce and the cities of the region in various historical periods: from the 16th century to World War II and the first post-war years. The author’s main interest is in publications published by local institutions (libraries, museums) and enthusiasts of regional history.